On the Problem of the Pre-Christian Finnic Personal Names in the Toponymy of the Russian North - Janne Saarikivi (Вопросы Ономастики, 2017)
The article addresses an understudied problem of pre-Christian Finnic personal names in the toponymy of the Russian North. In his observations, the author notes a considerable share of toponyms including such personal names recorded in the region, although in quantitative terms their number is still less than in other historical Finnic territories. The given study explores North Russian substrate toponyms derived from pre-Christian Finnic personal names in a broad typological setting, covering place names of a significant part of the European north-west (Finland, Karelia, Estonia, Latvia). The article focuses on eight components most frequently occurring in the toponyms: Iha-, Ikä-, Kaipa-, Leina-, Lempe-, Monta-, Usko-, Vihti-. The use of cartographic method allows the author to locate these ancient Finnic stems, which subsequently leads him to create the final map that correlates their distribution area with that of toponyms featuring the *hiite- stem, meaning ‘pre-Christian sanctuary’. This correlation gives a further testimony to the results of nominal stems mapping, since the *hiite- lexeme is proto-Finnic, which makes it highly plausible the toponyms derived from it can adhere to the era of the early settling of the Baltic Finns. According to the author’s conclusions, on the whole, the area of pre-Christian Finnic names in toponymy attests to the formerly vast territory of the Finnic tribes’ residence, which is now Russified in the north-east and Balticised in the south. The Russian North, in particular, shows the traces of several groups of the Finnic population; as the author suggests, along with Karelian and Vepsian native speakers, the region also used to have residents who spoke an unknown Finnic language.